An investigation of the influence of 3d printing defects on the tensile performance of ABS material. (2022) - Rifuggiato, Serena; Minetola, Paolo; Stiuso, Vito; Khandpur, Mankirat Singh; Fontana, Luca; Iuliano, Luca
Abstract: Recently, the popularity of 3d printing for industrial and consumer use has spread across many different sectors. For this reason, quality assurance of 3d printed parts is becoming increasingly important. The extrusion and layer-by-layer deposition of a polymer filament on the print bed can introduce defects such as pores and voids into the internal structure of 3d printed parts. The relation between 3d printing defects and tensile performance of 3d printed samples is studied in this paper. The study considers tensile specimens of acrylonitrile butadiene styrene (ABS) that were 3d printed by varying the infill strategy and percentage to simulate different levels of strength for the part. Before the tensile tests, the ABS samples were inspected by X-ray tomography to identify the presence of internal voids generated by the 3d printing process. For each sample, data and statistics about the internal defects were used for determining a relation with the tensile test results. The local deformation of the sample and the position of the final fracture were observed using a digital camera and digital image correlation (DIC). In most cases, the experimental results confirmed the matching between the presence of internal voids and the areas of high deformation. However, the position of the specimen fracture did not always coincide with the largest defects. Nevertheless, this study highlights the importance of non-destructive inspection in quality assurance of 3d printed parts when in-situ monitoring of the 3d printing process is not applied.